2015
DOI: 10.1371/journal.pone.0143720
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profile during Aphid Feeding in Chrysanthemum (Chrysanthemum morifolium)

Abstract: MicroRNAs (miRNAs) are important regulators of gene expression, affecting many biological processes. As yet, their roles in the response of chrysanthemum to aphid feeding have not been explored. Here, the identity and abundance of miRNAs induced by aphid infestation have been obtained using high-throughput Illumina sequencing platform. Three leaf small RNA libraries were generated, one from plants infested with the aphid Macrosiphoniella sanbourni (library A), one from plants with mock puncture treatment (libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
0
21
0
2
Order By: Relevance
“…In a study by Sattar et al [68], melon lines had different patterns of conserved and newly identified miRNA expression profiles during different stages of aphid herbivory. Also, Xia et al [69] found that different miRNAs were expressed in chrysanthemum during aphid feeding, with the greatest differences during early stages of aphid infestations (2-6 h of infestation). Here, we sampled 14 days after the beginning of infestation as our aim was not to study the effect of the insect, but that of the virus; the aphid-infested plants served only as a control to filter out the effect of the insect stress on the plants.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Sattar et al [68], melon lines had different patterns of conserved and newly identified miRNA expression profiles during different stages of aphid herbivory. Also, Xia et al [69] found that different miRNAs were expressed in chrysanthemum during aphid feeding, with the greatest differences during early stages of aphid infestations (2-6 h of infestation). Here, we sampled 14 days after the beginning of infestation as our aim was not to study the effect of the insect, but that of the virus; the aphid-infested plants served only as a control to filter out the effect of the insect stress on the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs play essential roles in plant development and stress signaling transduction pathways [10,12]. While the application of RNA-Seq methodologies to analyse the expression of ncRNA responses to biotic stresses in model plants is well-established, similar studies in cotton and reports linking changes in ncRNA abundance with plant-herbivore interactions are more limited [23,25,[32][33][34]. Despite the widespread use of traditional chemical-based strategies for whitefly control in cotton, epidemics remain prevalent worldwide [35].…”
Section: Discussionmentioning
confidence: 99%
“…ํŠนํžˆ miRNA์˜ target mRNA๊ฐ€ ๋Œ€๋ถ€๋ถ„์ด ์ „์‚ฌ์กฐ์ ˆ์ธ ์ž๋กœ ํ•˜์œ„์œ ์ „์ž์˜ ๋ฐœํ˜„์—๋„ ์˜ํ–ฅ์„ ์ฃผ๊ธฐ ๋•Œ๋ฌธ์— ๊ทธ ์˜ํ–ฅ ๋ ฅ์ด ๋งค์šฐ ์ปค์„œ ๊ตญํ™”์—์„œ๋„ NGS๋ฅผ ํ™œ์šฉํ•˜์—ฌ miRNA๊ฐ€ ์ „ ๊ฒŒ๋†ˆ ์ˆ˜์ค€์—์„œ ๋ถ„์„๋˜์—ˆ๋‹ค (Xia et al 2015;Zhang et al 2015). ์›์—ฐ๊ต์žก ํ›„์— ํ™•๋ณด๋œ 3์ข…๋ฅ˜์˜ ๋ฐฐ์—์„œ 228๊ฐœ์˜ miRNA๊ฐ€ ๋™์ •๋˜์—ˆ์œผ๋ฉฐ, ๊ฐ๊ฐ์˜ ๋ฐฐ์—์„œ ํŠน์ด์ ์œผ๋กœ ๋ฐœํ˜„๋˜๋Š” miRNA ๋„ ๊ทœ๋ช…๋˜์—ˆ๋‹ค .…”
Section: ์žฅ์ผ(Long-day) ์ฒ˜๋ฆฌ ์ค‘์ธ ์˜์–‘์ƒ์žฅ์ (Vegetative Buds) ๋‹จ์ผ ์„ ์‹œ์ž‘ํ•œ ํ›„ ํ™”์•„๋ถ„ํ™”๊ฐ€ unclassified
“…ํ•œํŽธ, ์ง„๋”ง๋ฌผ ํ˜น์€ ๋ฌผ๋ฆฌ์  ์ƒ์ฒ˜๊ฐ€ ๊ฐ€ํ•ด์ง„ ์‹คํ—˜๊ตฌ์™€ ๋Œ€์กฐ๊ตฌ์—์„œ miRNA๋ฅผ ๋ถ„์„ํ•˜์—ฌ ๋‹ค ๋ฅธ ์ข…์—์„œ๋„ ์ž˜ ๋ณด์กด๋œ 303๊ฐœ์˜ miRNA์™€ 234๊ฐœ์˜ ์‹ ๊ทœ miRNA๋ฅผ ๋ฐœ๊ฒฌํ•˜์—ฌ ์ตœ์ข… 537๊ฐœ์˜ miRNA๊ฐ€ ํ™•๋ณด๋˜์—ˆ๋‹ค. ํŠนํžˆ ๊ธฐ๋Šฅ์ด ์ž˜ ์•Œ๋ ค์ง„ miRNA ์ค‘์—์„œ miR159a, miR160a, miR393a ๊ฐ€ ์ง„๋”ง๋ฌผ์˜ ํ”ผํ•ด์— ์‹๋ฌผ์ด ํŠน์ด์ ์œผ๋กœ ๋ฐ˜์‘ํ•˜์˜€๋‹ค (Xia et al 2015). ๋‘ ๋…ผ๋ฌธ์—์„œ๋Š” miRNA์˜ target mRNA๋„ ์ผ๋ถ€ ๋ณด๊ณ  ํ•˜์˜€๋‹ค.…”
Section: ์žฅ์ผ(Long-day) ์ฒ˜๋ฆฌ ์ค‘์ธ ์˜์–‘์ƒ์žฅ์ (Vegetative Buds) ๋‹จ์ผ ์„ ์‹œ์ž‘ํ•œ ํ›„ ํ™”์•„๋ถ„ํ™”๊ฐ€ unclassified